(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The importance of the current study lies in the importance of the Tax policy that being considered one of the most important tools working on fulfilling the social, financial and economic goals and improving the investment environment in the country to become having the ability to activate the national economy. The current study has referred that ( Has the tax planning practiced by the Iraqi contribution companies led to increase the far-term tax outcome through getting benefit of the monetary funds and expansion in the economic activities or establishing new economic structures and consequently led to increase the tax? The hypothesis of the current study has indicated that the tax planning practiced by the Iraqi contribution contribute into encouraging the investment and new projects . The research aims toexplain the concept of the tax planning and its strategicimportance, and to what extent it depicts policies of expansion in investment. The research has concluded set of conclusions , most importantly, the Iraqi companies have agreed that the tax availability that could be obtained through the tax planning has been considered a factor for attracting the investment through paying attention to the nature of the monetary availabilities. As a result, the investment is considered as a main factor in defying the state’s economic center in the short-term an the main reason of the economic growth lies in creating jobs opportunities and production increase , technology development and exports expansion . Along withthe currencies ’ entry. Thus, all these factors reflect positively on the companies ’ contribution into the economy growth and taxplanning increase. Most important recommendations lie in the contribution of Iraqi companies to pay attention on the tax planning for reducing the tax regulations based on laws and achieving more profits and monetary availability to be used in fields of expansion and to open specialized companies or branches in and outside the country as to secure its work continuation and competition.